The economic and psychological impacts of covid-19: a exploratory study of the intersection of traditional and new vulnerable groups in South Korea - Yoonkyoung Lee; Taejin Lee (BMC, 2024)
Abstract Background The global impact of the COVID-19 pandemic has been extensive, disproportionately affecting various vulnerable populations. In addition to traditional vulnerable groups (TVGs) such as the elderly, women, people with lower education, disabled individuals, and low-income groups, new vulnerable groups (NVGs) have emerged, including essential workers, face-to-face workers, temporary workers, and the self-employed. This study focuses on exploring the economic and psychological effects of the pandemic on both traditional and newly recognized vulnerable groups within Korea. Methods The study employed multiple logistic regression using micro-level social survey data from Statistics Korea to calculate the odds ratio relating to two categories of vulnerable groups and their economic and mental health impacts. Additionally, through interaction term analysis, we tried to uncover the complex interrelationship between these non-vulnerable groups and target vulnerable groups. Results Both the newly identified and traditional vulnerable groups showed higher likelihood of facing economic and mental health challenges compared to non-vulnerable groups. The likelihood of encountering a decrease in income and work-related stress was 2.17 times higher (95% CI = 1.90-2.47) for NVGs, while those belonging to TVGs had a 1.75-fold increase (95% CI = 1.47-2.08). Moreover, female self-employed workers faced higher overall stress at 1.36 times greater risk (95% CI = 1.08-1.71), whereas elderly individuals who are self-employed exhibited lower odds of experiencing such stress at the intersection between TVGs and NVGs. Conclusion This research offers in-depth understanding of the diverse impacts of COVID-19 on at-risk groups. Furthermore, examinations that take into account interactions between NVGs and TVGs uncovered subtle effects within subgroup dynamics, suggesting that intersecting factors play a role in different levels of vulnerability. This provides valuable evidence for informing policy decisions and allocating resources.